2005
DOI: 10.1016/j.ejca.2005.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among long-term breast cancer survivors: A systematic review

Abstract: The aim of this study was to review the literature on quality of life among long-term survivors of breast cancer and identify the specific aspects of quality of life that were affected in these survivors. We also describe predictors of quality of life. Published research reports were included if they described the quality of life of breast cancer survivors diagnosed at least five years earlier. The methodological quality of the 10 selected studies, conducted between 1997 and 2004, was high according to a list … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
370
1
20

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 504 publications
(410 citation statements)
references
References 19 publications
19
370
1
20
Order By: Relevance
“…[9][10][11] Similar adaptations have recently been used in a systematic review of quality of life issues facing long-term breast cancer survivors. 12 Each article was independently scored by 2 authors (R.L.A. and J.N.C.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11] Similar adaptations have recently been used in a systematic review of quality of life issues facing long-term breast cancer survivors. 12 Each article was independently scored by 2 authors (R.L.A. and J.N.C.…”
Section: Methodsmentioning
confidence: 99%
“…The included articles were assessed methodically for quality, adapting the criteria by Mols et al 16 This scoring system uses a checklist of 10 items (Table 2). Studies with a score ≥8 were considered to be of high quality, a score in the range of 5 to 7 "moderate quality," and a score <5 "poor quality.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…In a systematic review of the quality of life among long-term breast cancer survivors, researchers found that social support (i.e., the number of social contacts and the amount of social involvement with friends and family) was an important predictor of the quality of life of cancer survivors. 28 If high levels of symptom intensity correspond with poorer levels of psychosocial functioning, symptom intensity may be an important predictor of the quality of life of patients with lower limb lymphedema. Similar to symptom intensity, patients reported the highest median levels of distress in the areas of health insurance, body image, and sexuality.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that breast cancer survivors with better health perceptions and who experienced less stress reported a better quality of life. 28 The importance of symptom distress as a potential predictor of the quality of life of patients with lower limb lymphedema should be explored. Qualitative studies are also needed to understand the unmet needs of patients with lower limb lymphedema in the psychosocial domain, with an emphasis on the area of patients' sexuality.…”
Section: Discussionmentioning
confidence: 99%